Investigation on the Interactions of NiCR and NiCR-2H with DNA. (30th June 2010) - Chitranshi, Priyanka; Chen, Chang-Nan; Jones, Patrick R.; Faridi, Jesika S.; Xue, Liang
Abstract : We report here a biophysical and biochemical approach to determine the differences in interactions of NiCR and NiCR-2H with DNA. Our goal is to determine whether such interactions are responsible for the recently observed differences in their cytotoxicity toward MCF-7 cancer cells. Viscosity measurement and fluorescence displacement titration indicated that both NiCR and NiCR-2H bind weakly to duplex DNA in the grooves. The coordination of NiCR-2H with the N-7 of 2 ′ -deoxyguanosine 5 ′ -monophosphate (5 ′ -dGMP) is stronger than that of NiCR as determined by H NMR. NiCR-2H, like NiCR, can selectively oxidize guanines present in distinctive DNA structures (e.g., bulges), and notably, NiCR-2H oxidizes guanines more efficiently than NiCR. In addition, UV and H NMR studies revealed that NiCR is oxidized into NiCR-2H in the presence of KHSO 5 at low molar ratios with respect to NiCR (≤ 4).